ΜMech micromechanics library. (October 2016) - Svoboda, Ladislav; Šulc, Stanislav; Janda, Tomáš; Vorel, Jan; Novák, Jan
Highlights: A first micromechanical library, as far as we are aware of Multiple inclusion problem based on polynomial Eshelby solution to the single inclusion problem. Consistent implementation of analytical homogenization schemes including a novel direct integration method. Abstract: The paper presents the project of an open source C/C++ library of analytical solutions to micromechanical fields within media with ellipsoidal heterogeneities. The solutions are based on Eshelby's stress-free, in general polynomial, eigenstrains and equivalent inclusion method. To some extent, the interactions among inclusions in a non-dilute medium are taken into account by means of the self-compatibility algorithm. Moreover, the library is furnished with a powerful I/O interface and conventional homogenization tools. Advantages and limitations of the implemented strategies are addressed through comparisons with reference solutions by means of the Finite Element Method.